Grey matter changes associated with deficit awareness in mild cognitive impairment: a voxel-based morphometry study - Ford, A.; Almeida, O.; Flicker, L.; Garrido, G.; Greenop, K.; Foster, Jonathan; Etheron-Beer, C.; Van Bockxmeer, F.; Lautenschlager, N. (IOS Press, 2014)
Reduced awareness of cognitive deficits in mild cognitive impairment (MCI) is associated with poorer outcomes although little is known about the anatomical correlates of this. We examined the association of insight and grey matter volume using a voxel-based morphometry approach in 65 volunteers with MCI and 55 healthy age-matched controls. Participants with MCI had multiple areas of subtle grey matter volume loss compared with controls, although these did not survive correction for multiple comparisons. These were predominantly in the temporal and anterior portions of the brain. Individuals with MCI did not differ from each other on a number of demographic and cognitive variables according to level of insight. Reduced awareness of cognitive deficits was associated with few differences in grey matter volume apart from a subtle loss of grey matter in the medial frontal gyri. Given the modest nature of these findings, the routine assessment of insight in non-clinical populations of individuals with MCI is therefore not supported. Prospective data in larger samples, however, would be helpful to clarify this further and determine if impaired insight predicts brain atrophy and cognitive decline.